“A deadly ball hath limited my life”: social constructs of the ‘Good Battlefield Death’ in the Revolutionary War - Talkington, Brittney (My University, 2014)
The “Good Death,” as it was understood in the eighteenth century, involved being aware that one was going to die, making one’s peace with God, and having family and friends at the bedside to receive wisdom and edification. The dying person occupied a space between worlds, according to popular belief, and could give clues to those present at the deathbed about the mysteries of God and sacred truths. The battlefield death, with its suddenness, lack of decorum, and unpredictability, did not fit into this pattern, and that posed a problem – as the experience of Trumbull’s sister illustrates – for the revolutionary generation. This paper will argue that revolutionary battles were of such scale, reached so deeply into the civilian population, and coincided so overtly with the birth of a new nation, that artists, writers, and chroniclers began to create a new version of the “Good Death” – a battlefield version of the good death – that could help to alleviate social stress. The “Good Battlefield Death,” conveyed through artistic works, narratives, funeral sermons, and oration, depicted the dying soldier as being able to ask forgiveness for sins and offer his soul to god, die with a comrade at his side, acknowledge those being left behind, receiving well wishes and respect from those present, giving advice to those still fighting, and signify the righteousness of the cause he was fighting for.
Keywords: Revolutionary War; Death; Mourning; Social construct; Joseph Warren; John Trumbull; Artistic works; Battlefield